Incentives dan Non Financial Perfomance Terhadap Kinerja Manajerial Dengan Komitmen Organisasional sebagai Variabel Moderasi - Reva Arsyilia; Anwar Hariyono (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Managers' primary responsibility is to boost the company's performance. With regards to hope hypothesis, the job of supervisors as leaders features the assumption that administrators who have adequate administrative information and abilities will actually want to reasonably tackle business issues. In the possibility aspect, this study investigates the impact of motivations and nonfinancial execution on administrative execution with the comprehension that administration approaches can affect administrative execution. The SMART-PLS application is used to conduct a quantitative analysis of the questionnaire data for the research method. The findings demonstrated that managerial performance was significantly influenced by incentives and nonfinancial performance, with organizational commitment unable to moderate the relationship.